2012
DOI: 10.1111/j.1469-8749.2012.04305.x
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation in children with intractable epilepsy: a randomized controlled trial

Abstract: AED Antiepileptic drug VNS Vagus nerve stimulationAIM The aim of this study was to evaluate the effects of vagus nerve stimulation (VNS) in children with intractable epilepsy on seizure frequency and severity and in terms of tolerability and safety.METHOD In this study, the first randomized active controlled trial of its kind in children, 41 children (23 males; 18 females; mean age at implantation 11y 2mo, SD 4y 2mo, range 3y 10mo-17y 8mo) were included. Thirty-five participants had localization-related epilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
94
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 48 publications
0
94
0
6
Order By: Relevance
“…All were carried out in patients with drug‐resistant epilepsy, although the extent of epilepsy characterization was variable across studies: two studies evaluated patients with drug‐resistant mesial TLE,12, 34 five specified “partial” or “focal” epilepsy in their study criteria,11, 14, 18, 32, 33 one targeted adults with malformations of cortical development,13 and the rest required only “medically refractory seizures,” including two that explicitly included patients with generalized epilepsy 6, 17. Several RCTs (5/12) evaluated VNS (whether implanted9, 14, 17, 31, 32 or transcutaneous6). Two evaluated HS (implanted34 or transcranial12), and the rest individually evaluated CS,35 TNS,11 rTMS,13 thalamic stimulation,33 and RNS 10, 16, 18.…”
Section: The Evidence For Neuromodulationmentioning
confidence: 99%
See 3 more Smart Citations
“…All were carried out in patients with drug‐resistant epilepsy, although the extent of epilepsy characterization was variable across studies: two studies evaluated patients with drug‐resistant mesial TLE,12, 34 five specified “partial” or “focal” epilepsy in their study criteria,11, 14, 18, 32, 33 one targeted adults with malformations of cortical development,13 and the rest required only “medically refractory seizures,” including two that explicitly included patients with generalized epilepsy 6, 17. Several RCTs (5/12) evaluated VNS (whether implanted9, 14, 17, 31, 32 or transcutaneous6). Two evaluated HS (implanted34 or transcranial12), and the rest individually evaluated CS,35 TNS,11 rTMS,13 thalamic stimulation,33 and RNS 10, 16, 18.…”
Section: The Evidence For Neuromodulationmentioning
confidence: 99%
“…Since then, open‐label extensions of these trials and multiple observational studies have reported further reductions in seizure frequency fueling support for the use of this device 7, 8, 36. However, the one available pediatric RCT17 did not show a seizure control benefit to VNS (responder rate of 16% in high‐ vs. 21% in low‐output stimulation), and the one prospective RCT comparing VNS to medical therapy, rather than comparing high to low settings of stimulation as done previously, did not show any difference in seizure frequency or responder rates between the treatment and control arms 32. Complications of VNS placement included hoarseness (30%), dyspnea (13%), and infection (12%) 14, 31.…”
Section: The Evidence For Neuromodulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Management of patients who have recurrent seizures and did not respond to medication or surgery is challenging. A number of double-blind randomized controlled trials have confirmed the therapeutic effects of Vagus Nerve Stimulation [VNS] for epilepsy [66][67][68][69]. A recent European long-term study [n=347] showed a 50% reduction in seizure frequency for up to 43.8% of patients [66].…”
Section: Neuromodulation For Epilepsymentioning
confidence: 99%